Pengaruh Kepemimpinan, Motivasi Dan Budaya Organisasi Terhadap Kinerja Karyawan Di Rsud Kudungga Kabupaten Kutai Timur - Juanti, Juanti, M.Farid Wajdi, MM.PhD (2017)
The purpose of this study was to analyze the influence of leadership, motivation and organizational culture on employee performance at Kudungga Public Hospital - East Kutai partially. The study used survey methods, which are analyzed by validity and reliability, the classic assumption test, multiple linear regression analysis, t test and the coefficient of determination using SPSS for Windows version 16. Sample was taking 80 employees by using purposive sampling. It is concluded that leadership and organizational culture partial no effect on the performance of employees at Kudungga Public Hospital, while the motivational effect on the performance of employees at Kudungga Public Hospital - East Kutai. Keywords: organizational culture, leadership, employee performance, motivation.